2017
DOI: 10.1177/0734371x17718030
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Representation: Gender, Authority, and City Managers

Abstract: For the last 50 years, the U.S. government has worked to address the sex pay gap in the workforce. Nevertheless, the pay gap remains persistent across sectors and organizational hierarchies. This study investigates the direct and indirect effects of sex and authority profile on the pay gap of city managers in the United States. The study uses ordinary least squares (OLS) regression analysis to predict the relationship between a city manager’s sex and authority profile variables as well as the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
0
20
0
2
Order By: Relevance
“…The unlevel ground for women within their organizations has enormous repercussions for their career development (Alkadry, Bishu, and Ali 2019). Reflecting on the gendered experiences of women in our study, one can argue that when gendered performances in organizations are normalized and left unchallenged, they perpetuate inequities that have substantive implications for the professional lives of women with respect to power, economic benefits, and social position, hence compromising the “economic case” for gender equity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unlevel ground for women within their organizations has enormous repercussions for their career development (Alkadry, Bishu, and Ali 2019). Reflecting on the gendered experiences of women in our study, one can argue that when gendered performances in organizations are normalized and left unchallenged, they perpetuate inequities that have substantive implications for the professional lives of women with respect to power, economic benefits, and social position, hence compromising the “economic case” for gender equity.…”
Section: Discussionmentioning
confidence: 99%
“…In the federal government, women earn 90 cents for every dollar their male counterparts earn (Hatch Institute 2018). At the local level, the pay gap is present for women in city management roles even after accounting for human capital and organizational factors (Alkadry, Bishu, and Ali 2019). Similarly, Luo, Schleifer, and Hill (2019) report that women in policing earn 84 percent of the salary earned by their male counterparts.…”
mentioning
confidence: 99%
“…Furthermore, if employees are segregated by position, occupation, or administrative role—and the model includes controls for those segregating dimensions—then underlying differences by sex, race, or loyalty will not be detected, despite clear cause for concern (Alkadry, Bishu, & Ali, 2017; Arulampalam, Booth, & Bryan, 2007; Blau & Kahn, 2017; Smart, 1991; Smith, 2012). For example, if all the women are in one occupation and all the men in another, then a model with indicator variables for occupation would be unable to detect differences in compensation by sex.…”
Section: Applicationsmentioning
confidence: 99%
“…This article set out to explore if the men and women who make it to the top of the Danish civil service are alike when we analyse dimensions of their human capital. We took interest in this question because the literature on gender equality and gender representation in public organizations points to a lack of equality between men and women in senior executive positions (Bowling et al 2006; Alkadry et al 2017; Yu 2018) and because we know from a recent survey that this is also the case in one of the most gender‐equal countries in the world, Denmark (Ledelseskommissionen 2017). We further illustrated this by doing a pool analysis, which showed that gender differences at the executive level are not explained by the pool from which they are mainly recruited; rather the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Women and men have different career patterns in both the public and private sectors, and numerous studies have documented gender differences regarding pay and advancement (Bowling et al 2006; Alkadry et al 2017; Yu 2018). In a recent study, the Danish Leadership and Management Commission documented how, while women constitute 60 percent of the first‐line managers in Denmark, the share of women falls to 44 percent at the intermediate level and 36 percent at the senior management level (Ledelseskommissionen 2017, 20).…”
Section: Introductionmentioning
confidence: 99%